Effectiveness and tolerance of single tablet versus once daily multiple tablet regimens as first-line antiretroviral therapy - Results from a large french multicenter cohort study. - Laurent Cotte; Tristan Ferry; Pascal Pugliese; Marc-Antoine Valantin; Clotilde Allavena; André Cabié; Isabelle Poizot-Martin; David Rey; Claudine Duvivier; Antoine Cheret; Pierre Dellamonica; Pierre Pradat; et al. (PLoS ONE)
Objectives Pill burden during antiretroviral treatment (ART) is associated with worse adherence and impaired virological suppression. We compared the effectiveness, tolerance, and persistence on treatment of single tablet regimens (STRs) with non-STR once-daily regimens in patients receiving first-line ART. Methods Retrospective analysis of naïve HIV-1 infected patients prospectively enrolled in the French Dat'AIDS cohort and initiating first-line ART with STRs or once-daily non-STRs from 2004 to 2013. The primary outcome was time to treatment discontinuation defined by any change in the treatment regimen. STR and non-STR groups were compared controlling for baseline risk factors by inverse probability weighted treatment Cox analysis (IPWT) and propensity-score matching (PSM). Results Overall, 3212 patients (STR 499, non-STR 2713) were included. Median time to treatment discontinuation was shorter in non-STR patients than in STR patients, both in the IPWT (HR = 0.61, p<0.0001) and the PSM cohort (HR = 0.55, p<0.0001). This difference disappeared when censoring ART modification for simplification, both in the IPWT (HR = 0.97, p = 0.65) and the PSM cohort (HR = 0.91, p = 0.33). A lower rate of virological failure was observed with STRs than with non-STRs in both cohorts (HR = 0.23; p = 0.002 and HR = 0.22, p = 0.003, respectively). A lower rate of treatment modification for adverse event was observed with non-STRs in the IPWT cohort (HR = 1.46, p<0.0001), but not in the PSM cohort (HR = 1.22, p = 0.11). Conclusion First-line therapy with STRs was associated with a longer time to treatment discontinuation than with non-STRs. However, when ART modification for simplification was not considered as a failure, STRs and non-STRs were similar.